Mundane Populism: Politics, Practices and Discourses of Roma Oppression in Rural Slovakia - Škobla, Daniel; Filčák, Richard (Sociologia ruralis, 2020)
In this article, we explore populist politics, discourses and social practices regarding the ethnic Roma in the rural regions of eastern Slovakia. Our approach was guided by a theoretical discussion of right‐wing populism and social inequalities. Methodologically, we relied on Bourdieu's conceptual apparatus as a useful scholastic device to translate very practical data from interviews and observations into structured analytical information. The article is based on field research, in which we explored waste management practices in the municipality of Laborov. We came to the conclusion that essential components of right‐wing populism in Laborov rest on what we characterised as ongoing racialised stigmatisation, reconfiguring previously racially uncategorised issues into ethnic problems and thus, reinforcing the stigmatisation and oppression of the disempowered Roma minority groups.